FORGING DIGITAL BUSINESS TRUST: ETHICAL STRATEGIES FOR SUSTAINABLE BUSINESS - Qona'ah El Hasan; Adi Muhamad Muhsidi; Wachjuni; Dewi Sintya (Universitas Kuningan, 2025)
The rapid evolution of the digital landscape has positioned digital business trust as paramount for fostering sustainable relationships between businesses and stakeholders. Despite its clear benefits, including potential annual growth exceeding 10%, companies frequently encounter ethical dilemmas in data management and digital technology adoption, such as AI bias and non-transparent marketing. While transparent and ethical practices are known to enhance consumer trust, a significant gap remains in research specifically outlining comprehensive strategies for building long-term digital trust using robust systematic literature review (SLR) methodologies. This study addresses this gap by conducting an SLR to identify and analyze digital business ethics strategies contributing to trust and business sustainability. Employing Publish or Perish with Google Scholar, the search utilized keywords like